Analisis Komponen Fisik Terhadap Kemampuan Servis Panjang Permainan Bulutangkis SMA YP PGRI 1 Makassar - Achmad Karim; Andi Sahrul Jahrir; Keprinaldi Keprinaldi (Gerak: Journal of Physical Education, Sports, and Health, 2021)
This study aims to determine: (1) Is there a relationship between arm muscle strength and long service ability in badminton; (2) Is there a relationship between wrist flexibility and long service ability in badminton; (3) Is there a joint relationship between arm muscle strength and wrist flexibility on long service ability in badminton. This type of research is a correlational research. with quantitative research methods or how to take the sample that is by means of simple random sampling technique. The population in this study were all students of SMA YP PGRI 1 Makassar. The sample used was 30 male students. The data analysis technique of this research is descriptive analysis, correlation analysis, and regression analysis at the significance level = 0.05 through the SPSS 21 program. The results showed that: (1) There was a significant relationship between arm muscle strength and long service ability in badminton with a value of r = 0.747; (2) There is a significant relationship between wrist flexibility and long service ability in badminton with a value of r = 0.634; (3) There is a jointly significant relationship between arm muscle strength and wrist flexibility on long service ability in badminton with the determinant coefficient (